Delayed Presentation of Iliac Vein Injury: A Severe Complication at Retropubic Midurethral Sling Arm Removal - Pansy Uberoi; Forrest Jellison (Case Reports in Urology)
Midurethral slings are the most common treatment for female stress urinary incontinence. Perioperative vascular injuries during placement of a retropubic midurethral sling (RMUS) are uncommon but have been described. The objective of this case report is to describe a complication of delayed presentation from a vascular injury at the time of retropubic sling arm removal not previously documented in the literature. This life-threating complication should be considered and precautions should be taken at retropubic sling arm removal. Prevention is accomplished by proper visualization of pelvic vasculature and/or eliminating tension on sling before excision.